Development of Genially Learning Media in IPAS Lessons in Fourth Grade Elementary School - Muhammad Hadad; Arifin, M. Zainal; Sukmansa, Elly (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2025)
This study aims to analyze the feasibility of Genially-assisted learning media developed for IPAS subject in Grade IV of elementary school. The research was motivated by the limited integration of technology-based media at SD Kesatuan, Bogor, despite the rapid advancement of digital learning tools. The research employed a Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Research subjects involved fourth-grade students. The feasibility assessment was conducted through expert validation (material, media, and language) and student response questionnaires. The results show that the validation by material experts reached 96% (very feasible), media experts 96% (very feasible), and linguists 97% (very feasible). Meanwhile, students’ responses to the use of teaching media obtained 97% (very feasible). These findings indicate that Genially-assisted learning media are categorized as valid, practical, and feasible for implementation in IPAS learning. Therefore, this development provides an alternative digital-based instructional tool that supports effective and engaging learning in elementary schools.